A Tohu (Sign) to Open Our Eyes to the Realities of Indigenous Māori Registered Nurses: A Qualitative Study - Komene, Ebony; Gerrard, Debra; Pene, Bobbie; Parr, Jenny; Aspinall, Cath; Wilson, Denise (Wiley, 2023)
Aims Identify the experiences of Māori nurses and priorities for a Māori model of relational care working with Māori patients and their whānau (extended family network) in acute hospital services. Background Māori, the Indigenous peoples of Aotearoa (New Zealand), have a relational and holistic worldview fundamental to establishing relationships with Māori patients and their whānau. Increasing the Indigenous Māori nursing workforce can improve Māori patient experiences but is challenged by ongoing recruitment and retention issues. Design A qualitative Māori-centred research methodology with 12 Māori nurses. Methods Data were collected using wānanga (learning through discussion, deliberation and consideration) using he aha ō hikoi (journey mapping) and kōrero mai (storytelling). Inductive thematic analysis was undertaken using a mahi a roopū (group process) approach. This study was conducted between May 2022 and June 2022. Results Three key themes: (1) Māori first, nurse second, (2) Cultural loading and (3) Compromised realities were identified. Māori nurses' praxis used their complex cultural and clinical intelligence to engage in a mana-enhancing way (strengths-based) to improve the care delivery for whānau Māori during their hospitalization journey. Cultural loading meant Māori nurses were often burdened with unrecognized workloads as they provided care for Māori patients and whānau, which often compromised their cultural integrity. Conclusion Nurses' commitment to care for whānau and their assigned patient load created extra burdens and threatened their cultural integrity. Their experiences highlighted modes of practice rather than models of care required to improve healthcare delivery for Māori entering the hospital. These findings signal issues and areas nursing leaders need to heed, necessary for addressing the retention of Māori in nursing and improving workload equity.
Keywords: 1110 Nursing; Nursing; cultural intelligence; hauora; indigenous; inequity; māori health; modes of care; wānanga; well-being